LEGAL MECHANISMS OF ENVIRONMENTAL INFORMATION OPENNESS AND PUBLIC PARTICIPATION - Ismoilov Umirbek (Bright Mind Publishing, 2026)
This article analyzes the legal mechanisms of environmental information openness and public participation. Based on international legal standards, particularly the principles of the Aarhus Convention, as well as national legislation, the study examines access to environmental information, mechanisms of citizen participation in environmentally significant decision-making processes, and access to justice in environmental matters. The article also puts forward scientific proposals aimed at improving environmental legislation.
Keywords: Environmental information, public participation, environmental rights, transparency, Aarhus Convention, environmental expertise, mass media, environmental impact assessment (EIA/OVOS).